1995
DOI: 10.1063/1.468847
|View full text |Cite
|
Sign up to set email alerts
|

Study of bimetallic Pd–Pt clusters in both free and supported phases

Abstract: We study PdPt bimetallic clusters in both free and supported phases. These clusters have been produced with a laser vaporization source. Free clusters directly produced by the source are studied by time of flight mass spectrometry and photofragmentation technique. We observed a sequential evaporation of Pd atoms in the mixed clusters consistent with a palladium segregation process. This tendency has been also observed on supported particles from which the structure and the composition are determined by high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…2 that the Pd atoms are enriched in the surface shell covering the Pt atoms, which implies the surface segregation phenomenon of Pd atoms. This observation is in good agreement with the results from the experimental [13,14] and theoretical methods [15][16][17]. The richer Pd atoms on the surface enables the cluster surface energy to be minimized, due to the lower surface energy of Pd (125 $ 131 meV Å À2 ), compared with Pt (155 $ 159 meV Å À2 ) [16].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…2 that the Pd atoms are enriched in the surface shell covering the Pt atoms, which implies the surface segregation phenomenon of Pd atoms. This observation is in good agreement with the results from the experimental [13,14] and theoretical methods [15][16][17]. The richer Pd atoms on the surface enables the cluster surface energy to be minimized, due to the lower surface energy of Pd (125 $ 131 meV Å À2 ), compared with Pt (155 $ 159 meV Å À2 ) [16].…”
Section: Resultssupporting
confidence: 87%
“…It is reported that the catalytic activity depends on the structure of the bimetallic clusters. Rousset and coworkers observed a sequential evaporation of Pd atoms in the Pd-Pt bimetallic clusters consistent with a Pd segregation process by experimental methods [13]. Fiermans and coworkers evidenced Pd segregation to the surface of the supported bimetallic clusters with X-ray photoelectron spectroscopy [14].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In particular, there has been a significant amount of work at the level of sophisticated electronic structure calculations, 1,2,3 but these were often limited to small sizes due to the numerical effort involved. On a different scale of chemical complexity, many studies have been carried out using explicit, empirical force fields 4,5,6,7,8,9,10,11,12 in order to investigate the segregation properties of these clusters.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the calculated surface energies are somewhat underestimated [56] and the deviation increases with decreasing Z. This is also the case for Pd [57].…”
Section: Second Moment Approximation For Pd-pd Interactionsmentioning
confidence: 71%